2015
DOI: 10.1007/s00268-015-3127-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Approach for Primary Colorectal Cancer Improves Outcome of Patients Undergoing Combined Open Hepatic Resection for Liver Metastases

Abstract: Laparoscopic resection of colorectal cancer in patients undergoing simultaneous open resection of liver metastases is associated with a reduction of blood loss, morbidity, and postoperative hospital stay, without affecting oncologic radicality. Outcome is mainly conditioned by approach to intestinal surgery, rather than the extent of liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
0
25
1
Order By: Relevance
“…Initial screening of abstracts led to the exclusion of 383 articles. Besides, six were further excluded by a close scrutiny of remaining articles: 1 35 only included OLR, 3 duplicates 24,36,37 , 1 38 did not report outcomes of interest and 1 39 used radiofrequency ablation. Finally, 32 non-randomized comparative studies were included in our meta-analysis 20,26,27,4068 .
Figure 1Study selection flow chart according to PRISMA statement.
…”
Section: Resultsmentioning
confidence: 99%
“…Initial screening of abstracts led to the exclusion of 383 articles. Besides, six were further excluded by a close scrutiny of remaining articles: 1 35 only included OLR, 3 duplicates 24,36,37 , 1 38 did not report outcomes of interest and 1 39 used radiofrequency ablation. Finally, 32 non-randomized comparative studies were included in our meta-analysis 20,26,27,4068 .
Figure 1Study selection flow chart according to PRISMA statement.
…”
Section: Resultsmentioning
confidence: 99%
“…One recent study showed that laparoscopic minor hepatectomy was associated with a better survival outcome [28]. In the long run, the benefits of the no-touch tech- 8 The use of hemostatic agents in patients with cirrhosis 9 Laparoscopic approach to treating HCC in difficult locations nique, less blood loss, and less transfusion could be reflected by better overall and diseasefree survival.…”
Section: Evidence On Laparoscopic Liver Resection For Hccmentioning
confidence: 99%
“…Laparoscopic liver resection is becoming an accepted approach for liver cancers [5,6], particularly on liver metastases [7][8][9][10][11], after two international consensus conferences held in Louisville in 2008 [12] and Morioka in 2014 [13]. To date, there has been no randomized controlled trial published.…”
Section: Introductionmentioning
confidence: 99%
“…In properly selected patients, minimally invasive colorectal resections appear to be beneficial even if the hepatectomy is performed in open fashion. Several groups have shown decreased complication rates in patients selected for laparoscopic colorectal resections combined with open hepatectomy compared to those undergoing combined open colorectal and liver resections . Strategies that facilitate parenchyma‐sparing approaches (eg, partial lobectomy with or without microwave ablation), would be ideally suited for minimally invasive combined procedures.…”
Section: Treatment Sequencementioning
confidence: 99%
“…A staged approach to this operation is associated with higher rates of morbidity in some studies . Minimally invasive approaches to either operation may further improve these results . This is also a scenario in which up‐front surgery should be considered, especially for patients with low‐recurrence risk (CRS, ≤2) as preoperative chemotherapy is associated with higher postoperative complications and provides little survival benefit .…”
Section: Anatomic‐based Treatment Sequence Considerationsmentioning
confidence: 99%